Analisis Employee Engagement, Kepuasan Kerja Dan Komitmen Organisasional Terhadap Organizational Citizenship Behavior Perawat Rumah Sakit - Amandha Habsari Priyanto; Noor Arifin (Jurnal Bisnis, Manajemen, dan Akuntansi, 2025)
This study aims to analyze the effect of Employee Engagement, Job Satisfaction, and Organizational Commitment to Organizational Citizenship Behavior (OCB) on employees of Kartini Hospital Jepara. This study uses descriptive quantitative research with sample of 96 employees. Data analysis uses a multiple linear regression approach, data processing using the IBM SPSS version 26.0 application. The results of the study indicate that employee engagement, job satisfaction, and organizational commitment have a significant positive effect to organizational citizenship behavior, with an average t-count > t-table 1.661 and a sig value <0.05. This indicates that the higher the employee engagement, will the higher to carry out extra behavior at work. The higher the employee's job satisfaction, the more proactive they are in helping coworkers and contributing to a positive work environment. Then the better employees who have a high commitment to the organization tend to be more loyal and willing to do additional tasks which are the core of OCB behavior.